Reactions Of Gold And Sulfide Minerals In Cyanide Media - G. Deschênes; A. Pratt; P. Riveros (Society for Mining, Metallurgy & Exploration, 2003)
The effect of pyrite, pyrrhotite, chalcopyrite, realgar and arsenopyrite on gold dissolution in cyanide media was investigated. The cyanidation of synthetic gold ores in the presence of various concentrations of sulfides was studied under constant experimental conditions. A mineralogical analysis of the minerals was performed. The leaching kinetics were determined. The negative effect of sulfides on the gold dissolution rate varies with the sulfide mineral and decreases according to the following order: realgar > pyrrhotite > chalcopyrite > pyrite > arsenopyrite. The chemical characterization of gold and sulfide minerals surfaces using X-ray photoelectron spectroscopy (XPS) was undertaken to identify the mechanisms involved. XPS analysis showed that a passivation layer of sulfides, arsenic or iron compounds might form on the gold surface as a result of the dissolution of the sulfide minerals. Key words: Gold dissolution, Cyanidation, Effect of sulfides, Leaching kinetics